Design, Synthesis, Characterization, Molecular Docking, ADME Properties and In Vivo Antipsychotic Activity of Aripiprazole Related Drugs Candidates - Sekar, Selvarasu; Pazhamalai, Srinivasan; Ariharasivakumar, Ganesan; Gopalakrishnan, Mannathusamy (Letters in Drug Design & Discovery, 2017)
Background: A series of newly synthesized compounds structurally related to Aripiprazole and Brexpiprazole, atypical antipsychotic and antidepressant used clinically for the treatment of schizophrenia, depression and bipolar disorder have been prepared and characterized by Elemental analysis, FT-IR, 1H NMR, 13C NMR, HSQC (2D NMR) and Mass spectrometry. All the compounds have been docked against, human A2A Adenosine receptor, human β2-Adrenergic G-Protein Coupled Receptor (GPCR) and ADME properties ware also evaluated. Objective: We focused on screening the neuroleptic activity of the synthesized drug molecules with different anti-psychotic animal models. Methods: All the drug molecules (10mg/kg) and also standard drug Aripiprazole (5mg/kg) were administered to their individual groups with 8 different animal models. Docking studies were carried out by Schrodinger 9.5 software to predict the antipsychotic activity and the pharmacokinetic properties were subjected to QIKPROP3.7 (Qikprop) module of Schrödinger software to determine ADME property.. Results: Both the receptor and ligand interaction shows an excellent dock score. ADME properties were also evaluated in the desirable range; finally these compounds have orally drug-likeness property. The results basically pointed out the fact that mutually the test molecules and control group may have the property to improve the positive symptoms of schizophrenia by reducing the dopamine levels of dopaminergic neurons of the brain. Conclusion: Docked against the protein to determine the Binding Energy, Glides core, Hydrogen bond, Total Intermolecular Energy and Interacting residues. ADME properties have been determined and obey the Lipinski's rule of five for drug likeness property. The synthesized compounds are used against Aripiprazole as a standard drug. The result has shown a promising effect in reducing the positive symptoms of psychosis in rats by sinking the dopamine levels in the frontal cortical region of the brain.
Keywords: ADME properties